Teaching meaningful mathematics with the Computer Algebra System MAXIMA using the example of inequalities - Fuchs, Karl Josef (Teaching Mathematics and Computer Science, 2013)
The paper was originally motivated by the request to accentuate the meaningful contribution of inequalities in Mathematics Education. Additionally nationwide approved competences such as estimating come to the fore when organizing mathematical contents along some central Big Ideas. Not least the integration of computers enriches the reasonable discussion of inequalities by modern well accepted methodological principles. The freeware MAXIMA is used as Computer Algebra System (CAS) representatively.